Geomorphic Dating of Across‐Fault Gully Incision Reveals Time‐Invariant Late Quaternary Slip‐Rates at the Eastern Termination of the Altyn Tagh Fault. Issue 8 (21st April 2022) - Wieler, Nimrod; Mushkin, Amit; Zhang, Huiping; Sagy, Amir; Porat, Naomi; Shmilovitz, Yuval; Ren, Zhikun; Huang, Feipeng; Shi, Pilong; Liu, Jinrui; Shelef, Eitan
Abstract: Interpretation of fault slip‐rates inferred from tectonically offset fluvial landforms is often limited by uncertainties associated with difficulties to explicitly date fluvial incision across the fault. Here, we employed morphology‐based modeling to ameliorate this universal dating limitation for gullies that were differentially offset in a sinistral sense across the Altyn Tagh Fault near its eastern termination at ∼97°E. Using a stream‐power erosion model with locally calibrated coefficients we calculated across‐fault gully incision ages that decrease with offset magnitude, are up to threefold younger than the age of the terrace they incised and all‐together point toward time‐invariant slip. Luminescence dating of offset alluvial terraces at the same site suggests constant sinistral slip at 0.5 ± 0.1 mm/yr since 52 ± 4 ka. Our results suggest that the most juvenile phase of northeastward Pleistocene expansion of the Tibetan Plateau into previously stable parts of central Asia is marked by constant late Quaternary deformation rates. Plain Language Summary: Horizontally deflected streams in tectonically active landscapes are often used by geoscientists to infer fault slip‐rates over geologic timescales. Our results demonstrate the potentially high degree of uncertainty that may be associated with this approach because incision itself is hard to date and age control for the deflected streams is conventionally indirectly obtained from dating the surface they incise and/or sediments they accumulate. Here, we applied morphology‐based modeling of fluvial incision to address this dating limitation for deflected streams near the eastern termination of the Altyn Tagh Fault in central Asia. Explicit dating of fluvial incision revealed across‐fault incision ages that were threefold younger than the age of the alluvial terrace incised and constant horizontal slip‐rates that were similar to longer‐term late Quaternary slip‐rates we obtained at the same site using offset terrace boundaries and luminescence dating for age control. Our results suggest that the late Pleistocene expansion phase of the Tibetan plateau northeastwards into central Asia is characterized by constant rates of deformation during the late Quaternary. Key Points: Using a stream‐power erosion model with locally calibrated coefficients we calculated across‐fault gully incision ages Constant sinistral slip of 0.5 ± 0.1 mm/yr since 52 ± 4 ka is calculated for the eastern termination of the Altyn Tagh Fault Our results are consistent with episodic rather than continuous growth of the Tibetan plateau northeastwards into central Asia